Belize : 2008 Article IV Consultation; Staff Report; and Public Information Notice on the Executive Board Discussion by the Executive Director for Belize. (IMF Staff Country Reports; Country Report ;, 2008)
Belize's near-term macroeconomic prospects have improved over the past year. The main risks to growth and financial stability arise from fiscal challenges and deterioration in the global outlook. Despite data limitations that constrain the analysis, the Belize dollar appears broadly in line with fundamentals, and the external accounts are not a threat to external stability. Progress in consolidating the public sector's financial position needs to continue. A front-loaded fiscal adjustment is necessary to lower Belize's debt ratios and regain market access.